First record of Stenostomum sphagnetorum (Platyhelminthes, Catenulida) from India - Bharti, Daizy; Brusa, Francisco; Kumar, Santosh; Chandra, Kailash (Zootaxa, 2020)
Catenulida are mostly inhabitants of freshwater ecosystems, like ponds, streams, though the marine species are few (Larsson and Willems, 2010). About 110 species of catenulids are known worldwide, with most of the studies conducted in South America (Marcus, 1945a, 1945b; Noreña et al., 2005), North America (Kepner and Carter 1931; Nuttycombe and Waters, 1938) and Scandinavian Peninsula (Luther, 1960, Larsson and Willems, 2010; Larsson et al., 2008). The diversity of catenulids from India has not been studied intensively; however some reports on other turbellaria exists for the country (Annandale, 1912; Whitehouse, 1913; Kapadia, 1947; Basil and Fernando, 1975; Apte and Pitale, 2011; Kalita and Goswami, 2012; Venkataraman et al., 2015). The genus Stenostomum, however, has been studied extensively around the world with identification of over 60 species (Tyler et al., 2006-2016). This is first report of the genus from India. The present study was part of the project to catalogue the diversity of free living protozoan ciliates from the Hooghly stretch of the Ganga River during which the flatworms were found. The worms were studied based on the live observations, with recognition of characters which led to its identification. This study serves to fill knowledge gap in the freshwater flatworms from India.